ANALISIS OBSERVASI KEADAAN SISTEM SINGULAR LTI ATAS DEKOMPOSISI STANDAR - Suryowati, Kris (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2006)
The singular system LTI is called linear singular system time invariant which its not be influence of the time changes. It is assumed to be the system is regular and rank E< n, so can be transform to form the standard decomposition. Furthermore, we discuss characterization the singular state observer and there is determine the necessary and sufficient condition for the state observer singular of system. Suppose that first sub systems in the decomposition standard system is observable. Then singular system LTI has a singular state observer. Singular system has a singular state observer if and only if it is detectable.